Residents’ Opinion on Virus Mitigation: A Case of Barangay San Pablo, the Philippines - Cyndell Jzhaqiy Blett S. Carlet; Romel Andre S. Doria; Caesar Ean R. Imperial; Vanessa Kaye J. Liza; Anamarie G. Valdez (ASEAN Journal of Science and Engineering Education, 2021)
This study was engaged for assessing the approaches of the barangay officials in mitigating the virus spread in the area through the opinions and experiences of the residents. The study was directed to a new and relevant type of adversity for a virus outbreak that can test the capabilities of the leaders. We utilized phenomenology, wherein narratives have been gathered through interviews. We extracted 5 themes; Erring Situations, Awareness on Precautionary Measures, Approach among Residents, Inequality among Residents, and Discipline. The barangay officials have never failed in implementing necessary protocols. But the protocols may not be sufficient to attain victory. For instance, statements have suggested that constant evaluation through the area should be mandated, and most importantly, the barangay officials should essentially be the first to follow their implementations. Overall, this study impacted the residents by providing a platform to voice out the leadership they received during these trying times.